ANALYSIS OF PROCESS TIME AND COPPER SLAG REQUIREMENTS IN THE SHIP HULL BLASTING PROCESS - Ilham Dermawan, Muhammad; Tri, Tri Agung Kristiyono; Aditya, Bagus Kusuma (Department of Marine Engineering, Universitas Hang Tuah, 2026)
The blasting process in the shipping industry aims to clean the surface of the plate from dirt, rust, and mill scale, and provide surface roughness so that the paint layer can adhere well. In the blasting process, abrasive materials are often used once or twice, but in field practice, reused copper slag has been used as an abrasive material. This study aims to analyze the weight of abrasive material requirements and process time during the blasting process using the Analysis of Variance (ANOVA) method with variations in new copper slag use, reused copper slag 1 and 2 as abrasive materials reaching the standard cleanliness level of SA 2.5 and the surface roughness level according to the International Maritime Organization (IMO) Performance Standard for Protective Coatings (PSPC) 30 – 75 mikron and the International Organization for Standardization (ISO) 8501-1. The results of this study indicate that fresh copper slag and reused copper slag-1 exhibit lower effectiveness in the blasting process; both types of copper slag require a longer time to reach the SA 2.5 cleanliness standard, resulting in increased abrasive material requirements. On the other hand, reused copper slag-2 exhibits better performance with shorter blasting time and minimal abrasive material requirements in accordance with the ISO 8501-1 SA 2.5 cleanliness level.